OPTIMIZATION OF CULTIVATION CONDITION OF SUBTYPE H5 FLU VIRUS - Mailybayeva, A.; Nurpeisova, A.S.; Assanzhanova, N.N.; Kozhamkulov, Y.M.; Inkarbekov, D.A.; Abitaev, R.T.; Jekebekov, K.K.; Nurabayev, S.Sh.; Kassenov, M.M.; Khairullin, B.M.; Kydyrbayev, Zh.; Valdovska, A.; et al. (Scientific Journal of Pedagogy and Economics, 2020)
This study looks into optimal conditions for cultivating the recombinant strains of subtype H5 influenza virus. The study results in establishing optimal conditions (inoculation dose, incubation temperature, incubation time, and chicken embryos’ age) for growing the influenza virus. This study establishes optimum conditions for cultivating the A/Sichuan/26221/2014(H5N6)-PR8-IDCDC-RG42A and A/gyrfalcon/Washington/41088-6/2014(H5N8)-PR8-IDCDC-RG43A subtype H5 influenza virus recombinant strains in embryonated chicken eggs. Data on culturing influenza virus recombinant strains presented herein indicates that they can be used in developing subtype H5 highly-pathogenic avian influenza vaccines. The results of this research will serve as a basis for developing a new inactivated emulgated vaccine following the process previously used by RIBSP to design its commercial vaccine. These optimum conditions are an infective dose of 10000 EID50/0.2 cm3, an incubation temperature of 36±0.50С, an embryo age of 10 days for cultivating the recombinant strain A/Sichuan/26221/2014(H5N6)-PR8-IDCDC-RG42A. Using these culturing conditions allows a stable production of virus-containing materials with an infectivity level of not less than 8.45±0.24 log EID50/cm3, which is fully consistent with requirements for producing inactivated vaccines for avian influenza. And optimal conditions for growing recombinant strain A/gyrfalcon/Washington/41088-6/2014(H5N8)-PR8-IDCDC-RG43A in 10 days embryonated chicken eggs with the infective dose 100000 EID50 in the incubation temperature 350С. These optimum conditions are helping culturing a stable production of virus-containing materials with an infectivity level of not less than 8.74±0.06 log EID50/cm3, which is fully consistent with requirements for producing inactivated vaccines for recombinant strain A/gyrfalcon/Washington/41088-6/2014(H5N8)-PR8-IDCDC-RG43A. Аn optimum incubation time of 48 hours, and relative air humidity of 55±5% for cultivating both recombinant strains.